The Glass Beads of Anglo-Saxon England - Guido, Margaret (Reports of the Research Committee of the Society of Antiquaries of London, 1999)
This book discusses the glass beads of early medieval (Anglo-Saxon) England. It provides a visual classification of the more definitive and diagnostic types. Supported by colour plates, line illustrations, and distribution maps, it describes the main types and lists their occurrences, principally as personal effects in grave complexes.